Effect Of Fused Deposition Modelling Fabrication Parameters On The Tensile Properties Of Acrylonitrile Butadiene Styrene - Chua, Jing Ting (Universiti Sains Malaysia, 2018)
In this study, the effect of raster orientation (0’/90’, 30’ /120’ and 45’ /135’) and printing temperature (220’C, 230’C, 240’C and 250’C) on the tensile properties of fused deposition modelling (FDM) fabricated acrylonitrile butadiene styrene (ABS) were investigated. The FDM specimen was fabricated and modelled according to the ASTM D638 Type I for both mechanical test and finite element analysis (FEA) using ANSYS software. Tensile properties were measured and employed further in FEA. The morphological characteristics of the fractured surface of specimens were examined using tabletop scanning electron microscopy (SEM). Thermal stability analysis on ABS was also done using thermogravimetric analysis (TGA) from room temperature to 250’C. The stress-strain curve, tensile strength, elongation at break, and Young’s modulus were analysed. It was observed that significant influence of raster orientation and printing temperature of FDM on tensile properties of the produced ABS samples. The FDM fabricated ABS exhibited slightly ductile behaviour and becoming more obvious from 0’ /90’ to 45’ /135’ . The fractured surfaces of ABS fabricated at 0’ /90’ raster orientation and 220’C, 230’C and 250’C printing temperature were smooth and flat, which indicated brittle failure. Meanwhile, ABS fabricated at 30’ /120’ and 45’/135’ raster orientation and 240’C printing temperature had rough and irregular fractured surface, which indicated ductile failure. Thermal stability of ABS at 250’C was proved to be low. The best tensile properties were found to be at raster orientation of 0’ /90’ and printing temperature of 240’C. It also observed that ANSYS simulation has good agreement with experimental result and able to predict the tensile performance of FDM fabricated ABS.